Advances in Smart Vehicular Technology, Transportation, Communication and Applications Proceedings of the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, November 6-8, 2017, Kaohsiung, Taiwan (Smart Innovation, Systems and Technologies,, 2018)
This book presents papers from the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications (VTCA 2017). Held from 6 to 8 November 2017 in Kaohsiung, Taiwan, the conference was co-sponsored by Springer, Fujian University of Technology in China, Fujian Provincial Key Laboratory of Digital Equipment, Fujian Provincial Key Lab of Big Data Mining and Applications, and National Kaohsiung University of Applied Sciences in Taiwan. The book is a valuable resource for researchers and professionals engaged in all areas of smart vehicular technology, vehicular transportation, vehicular communication, and applications.